Stock valuation through long-term financial multiples analysis - Arana Barbier, Pablo José (Pontificia Universidad Católica del Perú, 2020)
There is still a debate regarding which valuation multiples can estimate the price of a stock. Nevertheless, previous findings have not been considered in recent research, specifically geographic and company size delimitations, particularly for an emerging country. That leaves the valuation based on multiples still in an “exploratory” phase that targets multiples randomly. Besides, statistical validations have been left aside in several cases, and there is a lack of longterm valuation analysis that leads to understand the behavior of those multiples. The purpose of this investigation is to determine how strongly do the main valuation multiples explain the price of the stock in an emerging country such as Peru, through a panel data multiple linear regression, using two models: one composed by the most preferred valuation multiples among the literature, and the other one composed by those used by investigations in emerging countries. Also, a set of specific delimitations based on the literature are considered. The study has a quantitative approach, an explanatory scope, a longitudinal design and is non-experimental. The research is significant because its main findings: (a) the model composed by valuation multiples from emerging countries’ studies proves to be considerably stronger, (b) it can be reduced to a very short but statistically solvent model, and (c) a novel dummy variable is proposed and validated: the commodity-related business. The study will promote further debate and research regarding stock valuation in emerging versus developed countries.

Aún existe un debate respecto a qué múltiplos de valorización pueden estimar el precio de las acciones. Sin embargo, los hallazgos previos no han sido considerados en recientes investigaciones, específicamente delimitaciones geográficas y de tamaño de empresa, particularmente para países emergentes. Ello deja a la valorización de acciones basada en múltiplos en una fase “exploratoria” que apunta a múltiplos de valorización aleatoria. Además, hay validaciones estadísticas que han sido dejadas de lado en muchos casos, y faltan análisis de valorización de acciones a largo plazo que lleven a la comprensión del comportamiento de dichos múltiplos. El propósito de esta investigación es determinar qué tan fuertemente los principals múltiplos de valorización explican el precio de las acciones en un mercado emergente como Perú, a través de una regresión lineal múltiple de tipo panel data, utilizando dos modelos: uno compuesto por los múltiplos de valorización preferidos por la literatura, y el otro compuesto por aquellos utilizados en investigaciones en países emergentes. Además, un conjunto de delimitaciones específicas basadas en la literatura fueron consideradas. El estudio tiene un alcance cuantitativo, un enfoque explicativo, un diseño longitudinal y es no experimental. La investigación es significativa por sus principales hallazgos: (a) el modelo compuesto por los múltiplos de valorización de estudios de países emergentes probó ser considerablemente más fuerte, (b) el modelo puede ser reducido a uno muy corto pero estadísticamente solvente, y (c) una nueva variable dummy es propuesta y validada: empresas vinculadas a commodities. El estudio promoverá mayor debate e investigación respecto a la valorización de acciones en países emergentes versus países desarrollados.
Keywords: Mercado de capitales; https://purl.org/pe-repo/ocde/ford#5.02.04